Implementasi Model Pembelajaran Berbasis Masalah pada Pembelajaran IPA di Kelas V SD N Batu 1 Tahun Pelajaran 2022/2023 - Zuhrotul Muna; Joko Sulianto; A.Y. Soegeng (STKIP Andi Matappa Pangkep, 2022)
The purpose of this study is to describe the design of the Learning Implementation Plan with a problem-based model, describe the implementation of a problem-based model in science learning, and describe the responses of students during learning with a problem-based model in science learning in class V SD N Batu 1. This study uses a qualitative method. Data collection techniques in this study were carried out by means of observation, interviews, questionnaires and documentation. Data analysis was carried out in stages, namely data reduction, data display and conclusion data. Based on the results of the study, it showed that the implementation of the problem-based model in science learning in class V SD N Batu 1 went well and was in accordance with the theory of the Agency for Human Resources Development of Education and Culture and Education Quality Assurance of the Ministry of Education and Culture. The teacher has implemented all the stages or steps of the problem-based learning model, namely: orienting students to problems, organizing students to learn, guiding individual and group investigations, developing and presenting work, as well as analyzing and evaluating the problem solving process.